Critical Perspectives on J. M. Coetzee
XVI, 246 p.
Keywords: Critical Perspectives on J.M. Coetzee is one of the first collections of critical essays on this major contemporary writer. The essays, written by an international cast of contributors, adopt a variety of approaches to Coetzee's often controversial work, taking care to place that work within its wider cultural context. Contributions include essays of more general import, ranging across Coetzee's oeuvre, as well as essays that analyse in more detail individual Coetzee novels. The collection also includes a preface by Coetzee's fellow South African, the internationally acclaimed writer Nadine Gordimer.